Modification method for improving oxidation resistance of aluminide cladding coating

By adding NH4Cl, Ti and Hf elements to the aluminide coating, and using laser cladding process and natural air-drying curing process, the problem of reduced oxidation resistance of the aluminide coating under high temperature environments is solved, and the oxidation and peeling resistance of the coating is significantly improved.

CN119753668APending Publication Date: 2025-04-04HUANENG HUNAN YUEYANG POWER GENERATION CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411887673.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing aluminide coatings are prone to problems such as reduced oxidation resistance and film peeling in long-term service and high-temperature environments, resulting in reduced oxidation resistance.

Method used

The solid phase powder is modified by adding halide NH4Cl to the slurry components and introducing Ti and Hf elements, and aluminide cladding coating is prepared by laser cladding. Combined with natural air-drying and medium-low temperature curing processes, the viscosity and anti-peeling properties of the coating are enhanced.

Benefits of technology

It significantly improves the oxidation resistance and peeling resistance of the aluminum coated coating, enhances the bonding strength between the coating and the substrate, improves the oxidation resistance in high-temperature steam oxidation test, and achieves the effect of a complete oxidation level.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753668A_ABST
    Figure CN119753668A_ABST
Patent Text Reader

Abstract

The invention discloses a modification method for improving oxidation resistance of an aluminide cladding coating, which comprises the following steps: cleaning and preheating the surface of a workpiece to be plated, uniformly spraying cladding slurry onto the surface of the workpiece, air-drying and curing at medium temperature, and carrying out laser cladding to obtain the aluminide cladding coating, wherein the solid-phase cladding powder comprises the following components in percentage by mass: 60 to 80 percent of FeAl, 15 to 30 percent of Al, 0 to 5 percent of Ti, 0 to 5 percent of Hf and 2 to 7 percent of NH4Cl; according to the modification method for improving the oxidation resistance of the aluminide cladding coating, the prepared infiltrated layer is uniform in organization structure, moderate in thickness, sufficient in Al atom diffusion, good in metallurgical bonding with a base body and not prone to falling off, and the service life of the infiltrated layer is prolonged. The method is suitable for austenitic steel and high-temperature alloy parts for workpieces with large length-diameter ratios and various complex shapes, such as large boilers and oil and gas field transportation pipelines, and has excellent industrial batch production benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material surface alloying and coating preparation, and specifically relates to a modification method for improving the oxidation resistance of an aluminide cladding coating. Background Art

[0002] The economic losses caused by corrosion problems each year account for 3-4% of the gross domestic product, resulting in economic losses of up to 2 trillion yuan. Among them, the corrosion of large aspect ratio flow components used in high-temperature fields such as electricity, energy storage, and petrochemicals has become a common industry problem and technical pain point that restricts the safe production and operation of the entire energy equipment, resulting in huge losses. Taking the power industry as an example, pipe blockage and pipe burst accidents caused by scale problems on the inner wall of flow components account for more than 50% of boiler non-stop accidents, resulting in an increase of more than 20% in the operating cost and material cost of the unit; therefore, research and development of anti-oxidation and corrosion-resistant technologies suitable for the inner and outer wall surfaces of pipes used in boiler units has important practical significance.

[0003] At present, Xi'an Thermal Engineering Research Institute has developed a high-temperature anti-oxidation coating preparation technology suitable for the large aspect ratio structural characteristics, high temperature, long time and low stress service environment of the flow-through components of energy equipment, mainly based on aluminide coating; in the actual unit operation test, the aluminide coating also showed excellent anti-oxidation service performance.

[0004] However, with the extension of service time, the increase of unit power and the complexity of the service environment, a single aluminide coating will inevitably face the phenomenon of decreased oxidation resistance and film peeling. In addition, after long-term service, the Al content of the film decreases, and the density and uniformity of the oxide film will also be lost, reducing the oxidation resistance of the coating. Therefore, it is necessary to develop a new type of anti-oxidation coating preparation technology and process with excellent oxidation resistance and anti-stripping ability, suitable for various complex-shaped workpieces with large aspect ratios. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a modification method for improving the oxidation resistance of an aluminide cladding coating.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: a modification method for improving the oxidation resistance of an aluminide cladding coating, characterized in that: solid-phase cladding powder and liquid-phase binder are weighed and prepared according to a mass ratio, and cladding slurries of different proportions are prepared after stirring and ball milling for standby use;

[0009] The workpiece to be plated is cleaned and preheated, and then the cladding slurry is evenly sprayed onto the workpiece surface, and dried and solidified after spraying;

[0010] The workpiece after the spray coating is solidified is placed in an inert atmosphere for laser cladding, and an aluminide cladding coating is obtained after cooling, and the cladding residue is treated.

[0011] As a preferred embodiment of the modification method of the present invention, the infiltration source of the solid phase cladding powder is FeAl and Al powder, the activator is NH4Cl, the modifiers are Ti and Hf, and the binder is ethyl acetate; the FeAl, Al, Ti, and Hf powders are sieved through a 1000 mesh sieve.

[0012] As a preferred embodiment of the modification method of the present invention, the preparation method of the solid phase cladding powder comprises weighing the solid phase components according to mass percentage, including FeAl 60-80%, Al 15-30%, Ti 0-5%, Hf0-5% and NH4Cl 2-7%, the total mass of the solid phase components being maintained at 100%, and then mixing by ball milling in a planetary ball mill, the ball milling speed being 350-400rpm, and the time being 12-24h.

[0013] As a preferred embodiment of the modification method described in the present invention, the cladding slurry preparation method includes adding the binder ethyl acetate to the uniformly mixed solid phase powder at a mass ratio of 10 to 30% of the solid phase component, stirring it for 2 to 4 hours and then placing it in a planetary ball mill for ball milling mixing, the ball milling speed is 350 to 400 rpm, and the time is 8 to 12 hours.

[0014] As a preferred embodiment of the modification method of the present invention, the preheating treatment is medium frequency preheating at 200-250°C for 30-60 minutes.

[0015] As a preferred solution of the modification method of the present invention, the thickness of the prefabricated slurry layer is 1 to 5 mm, and the coating coverage is not less than 98%.

[0016] As a preferred embodiment of the modification method of the present invention, the prefabricated coating is dried by natural air drying for 24 to 48 hours, and the curing treatment is cured at 300 to 450° C. for 24 to 48 hours.

[0017] As a preferred embodiment of the modification method of the present invention, in the laser cladding, the laser power is 2-2.8KW, the scanning rate is 20-40mm / s, the spot diameter is 3-5mm, the workpiece rotation speed is 0-5r / min, and the Ar gas flow rate is 15-20L / min.

[0018] Another object of the present invention is to overcome the deficiencies in the prior art and produce an aluminide cladding coating.

[0019] As a preferred embodiment of the preparation method of the present invention, the preheating treatment is medium frequency preheating at 220°C for 30 to 60 minutes.

[0020] As a preferred embodiment of the preparation method of the present invention, the coating slurry is sprayed onto the surface of the workpiece, wherein the spraying pressure is 0.5-2MPa, the coating layer thickness is 0.1-5mm, and the coating coverage is not less than 98%.

[0021] As a preferred embodiment of the aluminide cladding coating of the present invention, the aluminide cladding coating has a uniform and dense structure, a thickness of 0.1 to 2.0 mm, an average Al content of 33%, and good metallurgical bonding with the substrate; in a 650°C steam cycle oxidation test, the oxidation weight gain after 800 hours is less than 1.0 mg / cm 2 , the antioxidant capacity is increased by 19 to 74 times compared with the parent material, reaching the complete oxidation level.

[0022] Beneficial effects of the present invention:

[0023] 1. The present invention adds halide NH4Cl to the slurry components, which has the effect of promoting penetration and activation, thereby improving the penetration rate and coating quality;

[0024] 2. The present invention can accelerate the transformation of θ~Al2O3 to α~Al2O3 and improve the film-base bonding force by introducing Ti element modification into the solid phase powder, and can form oxidation products with fine grains, thereby improving the "stickiness" of the oxide film and enhancing the antioxidant performance; the introduction of Hf element modification can aggregate at the oxide grain boundary and hinder further oxidation of the parent material, and its oxidation product HfO2 can pin the oxide film and enhance the oxide's anti-stripping performance; the segmented slurry curing process of natural air drying combined with medium and low temperature curing effectively avoids the problem of microcracks and tiny holes in the slurry layer caused by thermal stress during direct drying, and enhances the bonding strength between the slurry layer and the workpiece surface.

[0025] 3. The present invention prepares the coating by laser cladding process, which has concentrated heat, short action time, small thermal impact in the cladding area, and can reduce the adverse effects of the heat treatment process on the mechanical properties of the substrate;

[0026] 4. The present invention prepares the coating through an integrated laser cladding process production line. The coating has high production efficiency, controllable thickness, high process repeatability, and is extremely practical and universal. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0028] Figure 1 This is the tensile test specimen of the tile-shaped coating in Example 1 of the present invention (unit: mm).

[0029] Figure 2 This is the cross-sectional morphology of the coating in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0033] The raw materials used in the present invention come from:

[0034] FeAl powder was purchased from Noto Welding Materials Co., Ltd., spherical Al powder with a purity of 98% was purchased from Sinopharm Chemical Reagent Co., Ltd., with a specification of Alfa-041001, Ti powder with a purity of 93% was purchased from Sinopharm Chemical Reagent Co., Ltd., with a specification of Alfa-000681, Hf powder with a purity of 99.6% was purchased from Sinopharm Chemical Reagent Co., Ltd., with a specification of Alfa-010201, NH4Cl (analytical grade) was purchased from Sinopharm Chemical Reagent Co., Ltd., and ethyl acetate (analytical grade) was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0035] Instruments used in the embodiments of the present invention:

[0036] The vertical planetary ball mill was purchased from Changsha Miqi Instrument Equipment Co., Ltd., model YXQM-2L, the tubular furnace was purchased from Tianjin Bona Thermoelectric Furnace Co., Ltd., model BR-12NT-100 / 450, the laser cladding equipment was purchased from Jinweike Laser Technology Co., Ltd., model GKS-LC3008R, and the scanning electron microscope was purchased from Dongguan Sanben Precision Instrument Co., Ltd., model ZEISS SIGMA300;

[0037] The performance detection methods in the embodiments of the present invention are:

[0038] Cladding slurry bonding strength test: The bonding strength between the cladding slurry and the substrate is tested according to GB / T 31541-2015 "Fine ceramic interface tensile and shear bond strength test method cross method". The cladding slurry is evenly coated on the test surface of the two sample strips, and the two samples are bonded in a cross form. After drying and curing, the sample strip part of the sample is placed horizontally in the horizontal groove of the fixture, and the sample is clamped by adjusting the fixture with a nut. The U-shaped indenter is placed on the upper end of the sample to ensure uniform contact between the indenter and the sample. The strength test is carried out on the TDS-1 multi-functional desktop material performance tester, and the load is applied at a rate of 0.5mm / min until the interface is disconnected and the maximum load value at the break is recorded.

[0039] Coating thickness observation: The microscopic cross-sectional morphology of the coating sample after grinding and mechanical polishing was observed using a scanning electron microscope, and the thickness of the aluminide diffusion layer was measured using Image J software.

[0040] High temperature steam oxidation test:

[0041] The aluminide coating sample is placed in the constant temperature area of ​​the tube furnace. When the temperature in the tube furnace reaches the test temperature of 650°C, continuous water vapor is introduced into the reaction furnace through the water vapor generator at the front end. After the test, the oxidized coating sample is weighed with an electronic balance with an accuracy of 0.01 mg.

[0042] Example 1

[0043] The solid phase components, including 60% FeAl, 30% Al, 3% Ti, 5% Hf and 2% NH4Cl, were weighed in mass proportion and placed in a planetary ball mill for 12 hours at 400 rpm to obtain solid phase cladding powder; subsequently, 10% ethyl acetate was added and the mixture was stirred for 4 hours and then placed in a planetary ball mill for 12 hours at 400 rpm to obtain a uniformly mixed slurry, which is the cladding slurry.

[0044] Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 45 minutes at medium frequency, use spraying to pre-set the slurry layer thickness to 3mm, and keep the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 48 hours and cure it at 450°C for 48 hours.

[0045] The workpiece was placed under Ar for laser cladding, with a laser power of 2KW, a scanning rate of 40mm / s, a spot diameter of 3mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 15L / min. After completion, it was cooled to room temperature and the residue on the workpiece surface was flushed with high-pressure airflow.

[0046] Mechanical properties test of coating samples: According to GB / T 4338-2006 "High-temperature tensile test method for metallic materials", the high-temperature tensile properties of coating samples are tested. The sampling position and size of the tensile sample are as follows: Figure 1 The tensile test was carried out on a CMT5205 universal testing machine at a test temperature of 630°C and a strain rate of 2×10 –4 s / 1.

[0047] The processes of Examples 2 to 9 are the same as those of Example 1. Examples 1 to 9 maintain the same solid phase components and liquid phase binder ratio. The specific laser cladding process conditions are detailed in Table 1. Table 1 is the specific parameters of Examples 1 to 9 of the element-modified aluminide cladding coating preparation method. According to the preparation steps in the above Example 1 and the specific preparation parameters in the table, aluminide cladding coatings with different thicknesses and Al atomic contents can be obtained.

[0048] Table 1

[0049]

[0050]

[0051] By analyzing and studying the above examples, the thickness of the infiltration layer is measured to be about 0.24 to 1.67 mm. The specific results are shown in Table 1. The typical cross-sectional morphology of the coating of Example 1 is as follows: Figure 2 As shown in Table 1 and the cross-sectional morphology, it is found that the diffusion layer has a uniform structure, moderate thickness, sufficient diffusion of Al atoms, and a good metallurgical bond between the diffusion layer and the matrix, and is not easy to fall off.

[0052] The anti-oxidation performance of the infiltration layers prepared in Examples 1 to 9 in 650°C steam was tested. The mass change (mg / cm 2 The test results of ) are shown in Table 2.

[0053] Table 2

[0054]

[0055] It can be seen that the aluminide cladding coatings prepared in Examples 1, 5, and 6 showed oxidation weight loss in a pure water vapor environment at 650°C, indicating that the oxide film peeled off; the cladding coating prepared in Example 8 showed rapid oxidation after the oxidation time exceeded 300h, and the oxidation rate of the coating reached 0.00162mg / (cm 2 ·h), the coating has poor resistance to high-temperature steam oxidation; the cladding coating prepared in Example 4 has the lowest oxidation rate, and its oxidation weight gain trend conforms to the parabolic law. The coating has good oxidation resistance in a pure water vapor environment at 650°C, indicating that increasing the heat input of the laser cladding process increases the thickness of the prepared aluminide coating while also making the microstructure of the coating more uniform and dense, thereby improving the coating's resistance to high-temperature steam oxidation.

[0056] Example 10

[0057] The solid phase components, including 80% FeAl, 15% Al, 2% Ti, 2% Hf and 3% NH4Cl, were weighed according to the mass ratio, and placed in a planetary ball mill for ball milling at 350 rpm for 24 hours to obtain solid phase cladding powder; then, 30% ethyl acetate was added and fully stirred for 2 hours, and then placed in a planetary ball mill for ball milling at 400 rpm for 12 hours. After completion, a uniformly mixed slurry was obtained, which is the cladding slurry.

[0058] Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 200°C for 60 minutes at medium frequency, use spraying to pre-set the slurry layer thickness to 5mm, and keep the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 24 hours and cure it at 300°C for 48 hours.

[0059] The workpiece was placed under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 20mm / s, a spot diameter of 2mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 15L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was flushed with high-pressure airflow.

[0060] Embodiment 11

[0061] The solid phase components, including 65% FeAl, 25% Al, 5% Hf and 5% NH4Cl, were weighed according to the mass ratio, and placed in a planetary ball mill for ball milling at 400 rpm for 24 hours to obtain solid phase cladding powder; then, 20% ethyl acetate was added and fully stirred for 2 hours, and then placed in a planetary ball mill for ball milling at 350 rpm for 8 hours. After completion, a uniformly mixed slurry was obtained, which is the cladding slurry.

[0062] Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 30 minutes at medium frequency, use spraying to pre-set the slurry layer thickness to 2mm, and keep the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 24 hours and cure it at 450°C for 48 hours.

[0063] The workpiece was placed under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 40mm / s, a spot diameter of 3mm, a workpiece rotation speed of 2r / min, and an Ar gas flow rate of 15L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was flushed with high-pressure airflow.

[0064] Example 12

[0065] The solid phase components, including 65% FeAl, 25% Al, 5% Ti and 5% NH4Cl, were weighed according to the mass ratio, and placed in a planetary ball mill for 12 hours at 400 rpm to obtain solid phase cladding powder; then, 20% ethyl acetate was added and fully stirred for 2 hours, and then placed in a planetary ball mill for 12 hours at 350 rpm to obtain a uniformly mixed slurry, which is the cladding slurry.

[0066] Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 200°C for 60 minutes at medium frequency, use spraying to pre-set the slurry layer thickness to 5mm, and keep the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 24 hours and cure it at 400°C for 48 hours.

[0067] The workpiece was placed under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 20mm / s, a spot diameter of 3mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 15L / min. After completion, it was cooled to room temperature and the residue on the workpiece surface was flushed with high-pressure airflow.

[0068] Example 13

[0069] The solid phase components, including 60% FeAl, 25% Al, 3% Ti, 5% Hf and 7% NH4Cl, were weighed according to the mass ratio, and placed in a planetary ball mill for ball milling at 400 rpm for 24 hours to obtain solid phase cladding powder; then, 30% ethyl acetate was added and fully stirred for 2 hours, and then placed in a planetary ball mill for ball milling at 400 rpm for 12 hours. After completion, a uniformly mixed slurry was obtained, which is the cladding slurry.

[0070] Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 45 minutes at medium frequency, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece naturally for 24 hours and cure it at 450°C for 48 hours.

[0071] The workpiece was placed under Ar for laser cladding, with a laser power of 2KW, a scanning rate of 30mm / s, a spot diameter of 4mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 18L / min. After completion, it was cooled to room temperature and the residue on the workpiece surface was flushed with high-pressure airflow.

[0072] Embodiment 14

[0073] The solid phase components, including 70% FeAl, 20% Al, 2% Ti, 5% Hf and 3% NH4Cl, were weighed according to the mass ratio, and placed in a planetary ball mill for ball milling at 350 rpm for 12 hours to obtain solid phase cladding powder; then, 30% ethyl acetate was added and fully stirred for 4 hours, and then placed in a planetary ball mill for ball milling at 400 rpm for 8 hours. After completion, a uniformly mixed slurry was obtained, which is the cladding slurry.

[0074] Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 60 minutes at medium frequency, and use spraying to pre-set the slurry layer thickness to 4mm, keeping the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 36 hours and cure it at 450°C for 48 hours.

[0075] The workpiece was placed under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 40mm / s, a spot diameter of 5mm, a workpiece rotation speed of 4r / min, and an Ar gas flow rate of 20L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was flushed with high-pressure airflow.

[0076] Embodiment 15

[0077] The solid phase components, including 75% FeAl, 15% Al, 3% Ti, 3% Hf and 4% NH4Cl, were weighed in mass proportion and placed in a planetary ball mill for ball milling at 350 rpm for 24 h to obtain solid phase cladding powder; subsequently, 20% ethyl acetate was added and stirred thoroughly for 4 h and then placed in a planetary ball mill for ball milling at 400 rpm for 8 h. After completion, a uniformly mixed slurry was obtained, which is the cladding slurry.

[0078] Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 60 minutes at medium frequency, use spraying to pre-set the slurry layer thickness to 5mm, and keep the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 48 hours and cure it at 450°C for 48 hours.

[0079] The workpiece was placed under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 40mm / s, a spot diameter of 4mm, a workpiece rotation speed of 4r / min, and an Ar gas flow rate of 15L / min. After completion, it was cooled to room temperature and the residue on the workpiece surface was flushed with high-pressure airflow.

[0080] Example 16

[0081] The solid phase components, including 65% FeAl, 20% Al, 5% Ti, 5% Hf and 5% NH4Cl, were weighed according to the mass ratio, and placed in a planetary ball mill for ball milling at 400 rpm for 24 hours to obtain solid phase cladding powder; then, 30% ethyl acetate was added and fully stirred for 4 hours, and then placed in a planetary ball mill for ball milling at 400 rpm for 8 hours. After completion, a uniformly mixed slurry was obtained, which is the cladding slurry.

[0082] Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 60 minutes at medium frequency, use spraying to pre-set the slurry layer thickness to 5mm, and keep the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 24 hours and cure it at 450°C for 48 hours.

[0083] The workpiece was placed under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 35mm / s, a spot diameter of 4mm, a workpiece rotation speed of 2r / min, and an Ar gas flow rate of 18L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was flushed with high-pressure airflow.

[0084] The anti-oxidation performance of the infiltration layers prepared in Examples 10 to 16 in 650°C steam was tested. The mass change (mg / cm 2 The test results of ) are shown in Table 3.

[0085] Table 3

[0086]

[0087]

[0088] It can be seen that the aluminide cladding coatings prepared in Examples 11 and 16 showed accelerated oxidation after being oxidized in a pure water vapor environment at 650°C for 300h, and the oxidation rates of the coatings reached 0.00091 mg / (cm 2 ·h) and 0.00133mg / (cm 2 ·h), the coating has poor resistance to high-temperature steam oxidation; the oxidation weight gain trend of the coatings prepared in Examples 12 and 15 within 800h conforms to the linear law, and the oxidation rate of the coatings in a pure water vapor environment at 650°C is basically stable; the oxidation weight gain trend of the coatings prepared in Examples 10 and 13 conforms to the parabolic law, and the average oxidation weight gain rates within 800h are 0.00006mg / (cm 2 ·h) and 0.00007mg / (cm 2 h), under this condition, a complete anti-oxidation level is achieved, wherein the coating prepared in Example 10 has the lowest oxidation rate.

[0089] In summary, the effect of the preferred embodiment 10 is the best, followed by the embodiment 13.

[0090] Comparative Example 1

[0091] The difference between this comparative example and Example 10 is that the solid phase components are replaced by: 80% FeAl, 15% Al, 2% Ti and 3% NH4Cl.

[0092] Comparative Example 2

[0093] The difference between this comparative example and Example 10 is that the solid phase components are replaced by: 80% FeAl, 15% Al, 2% Hf and 3% NH4Cl.

[0094] Comparative Example 3

[0095] The difference between this comparative example and Example 10 is that the solid phase components are replaced by: 80% FeAl, 15% Al, 2% Pd and 3% NH4Cl.

[0096] Comparative Example 4

[0097] The difference between this comparative example and Example 10 is that the proportion of the solid phase components is replaced by: 80% FeAl, 15% Al, 0.5% Ti, 0.5% Hf and 4% NH4Cl.

[0098] Comparative Example 5

[0099] The difference between this comparative example and Example 10 is that the solid phase components are replaced by: 80% FeAl, 15% Al, 2.5% Ti, and 2.5% Hf.

[0100] Comparative Example 6

[0101] The difference between this comparative example and Example 10 is that the proportion of ethyl acetate is replaced by 10%.

[0102] Comparative Example 7

[0103] The difference between this comparative example and Example 10 is that the workpiece after the spraying treatment is cured at 450° C. for 72 hours.

[0104] Comparative Example 8

[0105] The difference between this comparative example and Example 10 is that the workpiece after curing is placed in a tube furnace at 950°C and subjected to high temperature aging treatment for 60 min under Ar gas protection.

[0106] The oxidation resistance of the prepared infiltration layers in Example 1, Examples 10 to 16 and Comparative Examples 1 to 8 was tested in 650°C steam. The mass change (mg / cm 2 ) are shown in Table 4.

[0107] Table 4

[0108]

[0109]

[0110] It can be seen that the oxidation weight gain trend of the aluminide cladding coatings prepared in Comparative Examples 1 and 2 within 800 h conforms to the linear law, and the oxidation rate of the coatings in a pure water vapor environment at 650 ° C is basically stable. The aluminide cladding coatings prepared in Comparative Examples 3 and 4 are oxidized in a pure water vapor environment at 650 ° C for 300 h and the oxidation rates of the coatings reach 0.00105 mg / (cm 2 ·h) and 0.00131mg / (cm 2 ·h). In summary, compared with the addition of Hf, Ti or Pd alone, the synergistic effect of Hf and Ti can reduce the oxidation rate of the prepared aluminide coating in 650°C water vapor by more than 30%, thereby further improving the coating's resistance to steam oxidation at high temperatures; in the coating prepared in Comparative Example 5, when the oxidation time exceeds 300h in a pure water vapor environment at 650°C, the stability of the oxide film deteriorates, oxidation weight loss begins to occur, and the oxide film peels off in large quantities, indicating that the addition of halide NH4Cl can effectively improve the antioxidant performance of the prepared aluminide coating.

[0111] Cross-section specimens were prepared according to the drying and curing processes of Example 10 and Comparative Example 7, respectively, and the bonding strength between the cladding slurry and the substrate was tested. The interfacial tensile bonding strength of the slurry layer prepared in Example 10 was 23.68 MPa, and the interfacial tensile bonding strength of the slurry layer prepared in Comparative Example 7 was 12.43 MPa, indicating that the segmented slurry curing process of natural air drying combined with medium and low temperature curing used in the present invention can effectively enhance the bonding strength between the slurry layer and the workpiece surface.

[0112] The high temperature tensile properties of the coating samples prepared in Example 10 and Comparative Example 8 were tested respectively. The tensile strength and elongation of the coating sample prepared in Example 10 were 349.8 MPa and 28.4%, respectively, and the relative difference with the substrate sample was no more than 3%. The tensile strength and elongation of the coating sample prepared in Comparative Example 7 were 308.6 MPa and 17.2%, respectively, indicating that the laser cladding process used in the present invention to prepare the coating can reduce the adverse effects of the heat treatment process on the mechanical properties of the substrate.

[0113] In summary, the present invention provides a coating for improving the oxidation resistance of an aluminide cladding coating. Under the conditions of adjusting the main process parameters such as the content of solid phase penetrant component, the content of modifying elements, the solid-liquid ratio of the slurry, the thickness of the coating layer and the heat treatment parameters, an aluminide cladding coating with a thickness of 0.1 to 2.0 mm and an average Al content of 33% is prepared, which has good metallurgical bonding with the substrate; the aluminide cladding coating obtained by the present invention has an oxidation weight gain of less than 1.0 mg / cm3 in a 650°C water vapor cycle oxidation test for 800 hours. 2 , the antioxidant capacity is improved by 19 to 74 times compared with the parent material, which means that the antioxidant capacity of the aluminide cladding coating prepared by the method of the present invention is effectively improved. The modification method of the present invention for improving the oxidation resistance of the aluminide cladding coating is suitable for austenitic steel and high-temperature alloy parts used in large boilers, oil and gas field transportation pipelines and various complex-shaped workpieces. It has strong practicality, high permeation rate, excellent membrane-base bonding, and excellent industrial mass production benefits.

[0114] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A modification method for improving the oxidation resistance of an aluminide cladding coating, characterized in that: Weigh and prepare solid-phase cladding powder and liquid-phase binder according to mass ratio, and prepare cladding slurries of different ratios after stirring and ball milling for use; The workpiece to be plated is cleaned and preheated, and then the cladding slurry is evenly sprayed onto the workpiece surface, and dried and solidified after spraying; The workpiece after the spray coating is solidified is placed in an inert atmosphere for laser cladding, and an aluminide cladding coating is obtained after cooling, and the cladding residue is treated.

2. The modification method according to claim 1, characterized in that: The infiltration source of the solid phase cladding powder is FeAl and Al powder, the activator is NH4Cl, the modifier is Ti and Hf, and the binder is ethyl acetate; wherein the FeAl, Al, Ti, and Hf powders are sieved through a 1000 mesh screen.

3. The modification method according to claim 1, characterized in that: The preparation method of the solid phase cladding powder comprises: weighing solid phase components according to mass percentage, including 60-80% of FeAl, 15-30% of Al, 0-5% of Ti, 0-5% of Hf and 2-7% of NH4Cl, with the total mass of the solid phase components maintained at 100%, and then mixing by ball milling in a planetary ball mill, with the ball milling speed being 350-400 rpm and the time being 12-24 hours.

4. The modification method according to claim 1, characterized in that: The cladding slurry preparation method comprises: adding a binder ethyl acetate to a uniformly mixed solid phase powder at a mass ratio of 10 to 30% of the solid phase component, stirring the mixture for 2 to 4 hours, and then placing the mixture in a planetary ball mill for ball milling at a ball milling speed of 350 to 400 rpm for 8 to 12 hours.

5. The modification method according to claim 1, characterized in that: The preheating treatment is medium frequency preheating at 200-250° C. for 30-60 minutes.

6. The modification method according to claim 1, characterized in that: The thickness of the prefabricated slurry layer is 1-5 mm, and the coating coverage is not less than 98%.

7. The modification method according to claim 1, characterized in that: The prefabricated coating is dried by natural air drying for 24 to 48 hours, and the curing treatment is cured at 300 to 450° C. for 24 to 48 hours.

8. The modification method according to claim 1, characterized in that: In the laser cladding, the laser power is 2-2.8KW, the scanning rate is 20-40mm / s, the spot diameter is 3-5mm, the workpiece rotation speed is 0-5r / min, and the Ar gas flow rate is 15-20L / min.

9. An aluminide cladding coating obtained by the modification method according to any one of claims 1 to 8.

10. The aluminide cladding coating according to claim 9, characterized in that: The aluminide cladding coating has a uniform and dense structure, a thickness of 0.1 to 2.0 mm, an average Al content of 33%, and good metallurgical bonding with the substrate; in a 650°C steam cycle oxidation test, the oxidation weight gain after 800 hours is less than 1.0 mg / cm 2 , the antioxidant capacity is increased by 19 to 74 times compared with the parent material, reaching the complete oxidation level.